2012
DOI: 10.1016/j.bbamem.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions and hemichannels in signal transmission, function and development of bone

Abstract: Gap junctional intercellular communication (GJIC) mediated by connexins, in particular connexin 43 (Cx43), plays important roles in regulating signal transmission among different bone cells and thereby regulates development, differentiation, modeling and remodeling of the bone. GJIC regulates osteoblast formation, differentiation, survival and apoptosis. Osteoclast formation and resorptive ability are also reported to be modulated by GJIC. Furthermore, osteocytes utilize GJIC to coordinate bone remodeling in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
109
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 184 publications
0
109
0
2
Order By: Relevance
“…The intracellular gap junctional communication among osteocytes, osteoblasts, and osteoclasts plays crucial roles in bone remodeling (38). Previous cellular studies have shown that lycopene inhibited osteoclast differentiation and activation, and facilitated osteoblast differentiation and proliferation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular gap junctional communication among osteocytes, osteoblasts, and osteoclasts plays crucial roles in bone remodeling (38). Previous cellular studies have shown that lycopene inhibited osteoclast differentiation and activation, and facilitated osteoblast differentiation and proliferation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…37 Osteoclast formation and resorptive ability are also reported to be modulated by gap junction. 2,16,28 But it still remains unknown whether this connexin-dependent behaviors of osteoclasts are involved with calcium response.…”
Section: Introductionmentioning
confidence: 99%
“…Cx43, encoded by the Gja1 gene, is the most ubiquitous gap junction protein expressed in bone cell types, including chondrocytes, osteoblasts, osteocytes, osteoclasts, and BMSCs [14, 16]. Cx43 plays important roles in regulating signal transmission among different bone cell types and thereby regulates development, differentiation, modeling and remodeling, as well as pathologies of bone [16-19].…”
Section: Introductionmentioning
confidence: 99%